Ruthenium nanoparticle-loaded black titanium dioxide composite material as well as preparation method and application thereof

By loading black titanium dioxide composites with ruthenium nanoparticles and using sodium borohydride modification to construct hindered Lewis acid-base pairs, the selectivity of the ruthenium-based catalyst is reversed, and carbon dioxide is efficiently reduced to carbon monoxide under normal pressure, solving the problem of carbon dioxide in the existing technology. It reduces the problems of selective regulation and high energy consumption and is efficient, controllable and environmentally friendly.

CN119346103AActive Publication Date: 2025-01-24TONGJI UNIV

Patent Information

Application Number
CN202411918007.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing carbon dioxide reduction technology relies on thermal catalytic reactions and requires a large amount of fossil energy to supply energy, which makes it difficult to achieve carbon neutrality. In addition, traditional ruthenium-based catalysts have insufficient product selective regulation, making it difficult to efficiently reduce carbon dioxide to carbon monoxide under normal pressure conditions.

Method used

Black titanium dioxide composite materials with load -load nanoparticles can be used to modify the electronic structure of titanium dioxide carrier through sodium borne sodium, and build a hindered Luisic acid alkali pair to reverse the selectivity of the catalyst catalyst to achieve carbon dioxide efficiently as carbon monoxide under normal pressure.

Benefits of technology

It significantly improves the controllability of the products of the carbon dioxide reduction reaction, with selectivity exceeding 99%, reducing the energy consumption and cost of traditional thermocatalytic technology, and solving the shortcomings of photocatalytic technology in carbon dioxide activation capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346103A_ABST
    Figure CN119346103A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon neutralization, and discloses a ruthenium nanoparticle-loaded black titanium dioxide composite material as well as a preparation method and application thereof. According to the catalyst, the electronic structure of titanium dioxide is modified and regulated through sodium borohydride, a unique Ti-H..Ti-OH hindered Lewis acid-base pair is formed, carbon dioxide is subjected to photo-thermal catalytic reduction to carbon monoxide at the temperature of 200 DEG C or above, the selectivity exceeds 99%, and reversal of methane selectivity of unmodified ruthenium nanoparticle loaded white titanium dioxide is achieved. The average particle size of ruthenium nanoparticles loaded on the surface of the catalyst is 2-5 nanometers, and the loading capacity is 0.5%-5%. The catalyst shows an excellent synergistic effect in photo-thermal catalysis, and an efficient solution is provided for high-value utilization of carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon dioxide reduction, and in particular relates to a black titanium dioxide composite material loaded with ruthenium nanoparticles, and a preparation method and application thereof. Background Art

[0002] Carbon dioxide is an important greenhouse gas and also a potential chemical and energy material. As an important intermediate in the earth's carbon cycle, carbon dioxide is not only a bridge between the inorganic and organic carbon cycles, but also an indispensable raw material for plant photosynthesis. A variety of high-value chemicals such as methane, methanol, and carbon monoxide can be produced by reducing carbon dioxide. Among them, carbon monoxide is not only an important component of synthesis gas, but also a basic raw material for the preparation of higher alkanes and other chemical products. It is widely used in industrial processes such as Fischer-Tropsch synthesis.

[0003] At present, the industrial technology for reducing carbon dioxide to produce high-value products such as methane or carbon monoxide mainly relies on thermal catalytic reactions. Carbon dioxide can be effectively converted into target products by using Fe-based, Co-based, Pt-based or Ru-based catalysts under high temperature and high pressure conditions. However, the thermal catalytic process requires a large amount of fossil energy to supply energy, which not only makes it difficult to achieve carbon neutrality throughout the process, but also causes additional carbon dioxide emissions due to the combustion of fossil energy. Therefore, the development of carbon dioxide reduction technology driven by clean energy is of great significance to alleviating climate change and energy crises.

[0004] As a clean and renewable energy source, solar energy has attracted widespread attention due to its abundance and sustainability. Although solar thermal power generation and water heater technologies are relatively mature, directly converting solar energy into chemical energy to drive reactions remains a technical challenge. Photothermal catalysis technology, as a comprehensive technology that combines the photoelectric effect and the thermal energy effect, can utilize full-spectrum sunlight to generate photogenerated carriers through high-frequency photons and heat the catalyst surface through low-frequency photons to achieve a synergistic catalytic effect. However, in the existing technology, how to achieve the selective reduction of carbon dioxide molecules through photothermal catalysis, especially how to regulate the selectivity between products such as methane and carbon monoxide, remains an unsolved core scientific problem.

[0005] Ruthenium-based catalysts are widely considered to be highly efficient catalysts for carbon dioxide reduction reactions, but the regulation of product selectivity is highly dependent on the properties of the carrier. Traditional ruthenium catalysts on unmodified carriers generally tend to produce methane, while the need to produce carbon monoxide requires precise regulation of the electronic structure and surface active sites of the carrier. If the product selectivity of ruthenium-based catalysts can be reversed by carrier modification, thereby efficiently reducing carbon dioxide to carbon monoxide under normal pressure conditions, it will greatly enhance the application potential of photothermal catalysis technology in the field of carbon neutrality and provide a new solution for green chemical synthesis. Summary of the invention

[0006] To solve the above technical problems, the present invention provides a black titanium dioxide composite material loaded with ruthenium nanoparticles, and a preparation method and application thereof. The present invention provides a catalyst that can efficiently focus sunlight, efficiently activate carbon dioxide, and significantly improve the selectivity of carbon dioxide reduction products. The present invention uses sunlight as the only energy input, and uses a xenon lamp light source to simulate sunlight during the laboratory testing phase. The catalyst in the present invention can efficiently utilize full-band sunlight, including ultraviolet, visible light and infrared bands, and drive the reduction reaction of carbon dioxide through the photothermal synergistic effect.

[0007] The first object of the present invention is to provide a black titanium dioxide composite material loaded with ruthenium nanoparticles, characterized in that black titanium dioxide is used as a carrier, and ruthenium nanoparticles are loaded on the surface of the carrier, and the surface of the carrier contains a Ti-H···Ti-OH hindered Lewis acid-base pair.

[0008] In some embodiments of the present invention, the loading amount of the ruthenium nanoparticles is 0.5wt%-5wt%; The average particle size of the ruthenium nanoparticles is 2-5 nanometers.

[0009] The second object of the present invention is to provide a method for preparing a black titanium dioxide composite material loaded with ruthenium nanoparticles, comprising the following steps: P25 titanium dioxide and a reducing agent are mixed, the resulting mixture is light-milled (for 20 to 40 minutes), and then heated and calcined to obtain a black powder; The obtained black powder is mixed with water for reaction, the solid-liquid separation is performed to obtain a solid phase, and the obtained solid phase is dried under light in an inert atmosphere to obtain modified titanium dioxide BTO; Dispersing modified titanium dioxide BTO in a ruthenium-containing precursor solution to obtain a suspension; removing the solvent in the suspension to obtain a precursor; The precursor is photo-reduced in a reducing atmosphere to obtain the black titanium dioxide composite material loaded with ruthenium nanoparticles.

[0010] In some embodiments of the present invention, the mass ratio of the p25 titanium dioxide to the reducing agent is 1:(2-4); The reducing agent is selected from one or more of sodium borohydride, potassium borohydride, lithium aluminum hydride, sodium hydride and lithium hydride; The heating calcination temperature is 200-500°C and the time is 10-120 minutes.

[0011] In some embodiments of the present invention, during the reaction of the black powder and water, the black powder reacts violently and releases heat, and releases a large amount of gas. After the gas release stops, the product is further washed at least three times by centrifugation with distilled water, and finally washed at least three times with ethanol.

[0012] In some embodiments of the present invention, the ruthenium-containing precursor in the ruthenium-containing precursor solution is selected from one or more of ruthenium dodecacarbonyl, ruthenium chloride, ruthenium acetylacetonate, and ruthenium acetate; The solvent of the ruthenium-containing precursor solution is selected from one or more of methanol, ethanol, tetrahydrofuran, acetone, and cyclohexane; The ruthenium concentration in the ruthenium-containing precursor solution is 100-2000 ppm; The inert gas in the inert atmosphere is selected from one or more of nitrogen, argon, helium and neon; The light source in the light drying is infrared light, and the light exposure time is 1 to 3 hours.

[0013] In some embodiments of the present invention, the mass ratio of ruthenium loaded in the modified titanium dioxide BTO is 0.1-5 wt %.

[0014] In some embodiments of the present invention, the reducing gas in the reducing atmosphere includes hydrogen and an inactive gas, and the inactive gas is selected from one or more of nitrogen, helium, argon, and neon; The volume ratio of hydrogen to inert gas is (3:1)-(1:3); The total gas flow rate in the reducing atmosphere is 50-100 mL / min; The temperature of light reduction is 200-280℃ and the time is 4-8h.

[0015] In the present invention, the method for removing the solvent from the suspension is to use a rotary distiller and to remove the solvent by vacuum distillation in a water bath at 40-60°C.

[0016] The third object of the present invention is to use the black titanium dioxide composite material loaded with ruthenium nanoparticles in the photothermal catalytic reduction of carbon dioxide to carbon monoxide.

[0017] In some embodiments of the present invention, a mixed gas of carbon dioxide and hydrogen is introduced into the photothermal catalytic reaction; Wherein, the volume ratio of carbon dioxide to hydrogen is (4:1)-(1:4); The reaction temperature in the photothermal catalytic reaction is greater than or equal to 200° C., and preferably 200-400° C. The temperature is controlled by a thermistor probe directly contacting the catalyst surface for testing, the gas flow is controlled by an electronic flow meter, and the reactor carrying the catalyst is made of quartz.

[0018] In some embodiments of the present invention, the black titanium dioxide composite material loaded with ruthenium nanoparticles needs to be activated before the photocatalytic reaction, and the activation conditions are: irradiation in a reducing atmosphere at 180-300° C. for 6-8 hours.

[0019] The core innovation of this invention is to modify and regulate the electronic structure of titanium dioxide (BTO) carrier by sodium borohydride, construct a unique hindered Lewis acid-base pair (Ti-H···Ti-OH), significantly reverse the selectivity of ruthenium-supported catalyst, and switch the main product of carbon dioxide reduction from methane to carbon monoxide, with a selectivity of more than 99%. The realization of this reverse selectivity not only overcomes the difficulty of traditional catalysts in controlling product distribution, but also greatly improves the performance stability and industrial applicability of catalysts in photothermal carbon dioxide reduction.

[0020] The catalyst of the present invention can achieve efficient light absorption and photothermal conversion. When only a xenon lamp light source is used as energy input, the catalyst surface temperature can be freely adjusted to 200-550°C to meet different reaction requirements. The photothermal synergistic catalytic properties of the catalyst of the present invention can efficiently and stably reduce carbon dioxide to carbon monoxide under normal pressure, while significantly reducing the problems of high energy consumption and high cost of traditional thermal catalytic technology and the shortcomings of existing photocatalytic technology in carbon dioxide activation ability.

[0021] In summary, the present invention significantly improves the product controllability of the carbon dioxide reduction reaction by reversing the selectivity of the catalyst design, provides a new idea for solar-driven carbon dioxide reduction technology, and has important environmental and energy significance.

[0022] The above technical solution of the present invention has the following advantages compared with the prior art: 1. Environmentally friendly driving mode. The use of solar energy for photothermal catalytic carbon dioxide reduction has the advantages of being environmentally friendly and low-cost. Since the catalyst in the present invention can make full use of the light energy of various bands of sunlight, and the light absorption capacity of the carrier black titanium dioxide is improved by modification with sodium borohydride, the absorption capacity of black titanium dioxide in the visible light and near-infrared light regions is stronger than that of white titanium oxide. This modification enables the catalyst of the present invention to control the reaction temperature on the catalyst surface to 200-400 degrees Celsius by regulating the light intensity when only focused sunlight is used, thereby achieving efficient solar energy utilization and photothermal conversion. The performance of its concentrated solar energy catalytic reduction of atmospheric carbon dioxide to carbon monoxide can reach more than 10 mmol carbon monoxide / (gram catalyst * hour), which greatly improves the efficiency of photothermal catalysis.

[0023] 2. Unique active site structure. Sodium borohydride modification forms unique surface hydroxyl Ti-OH and hydrogen-oxygen vacancies Ti-HOV in the base material BTO, where the hydrogen in Ti-HOV carries a partial negative charge and is a Lewis base; the hydrogen in Ti-OH carries a partial positive charge and is a Lewis acid, Ti-HOV and Ti-OH. The two are not connected by chemical bonds, but are discrete in space, forming a hindered Lewis acid-base pair Ti-HOV···Ti-OH. This active site can directly activate an oxygen atom in gaseous carbon dioxide and generate water and carbon monoxide. In a hydrogenated atmosphere, the ruthenium nanoparticles loaded on the surface of BTO can efficiently activate hydrogen to produce hydrogen overflow, which further hydrogenates the surface of BTO and replenishes the consumed Ti-HOV···Ti-OH.

[0024] 3. The selectivity of ruthenium-based catalysts has been reversed. The present invention reverses the selectivity of traditional ruthenium-based catalysts. Traditional ruthenium-based catalysts usually tend to selectively generate methane in the carbon dioxide reduction reaction, while the present invention optimizes the catalyst structure to enable it to exhibit extremely strong carbon monoxide selectivity during the reaction. Specifically, the hindered Lewis acid-base pair Ti-HOV···Ti-OH on the highly active carrier BTO quickly converts carbon dioxide into carbon monoxide, inhibits methanation on the ruthenium particles, and instead converts the ruthenium nanoparticles into hydrogen overflow centers to replenish the consumed Ti-HOV···Ti-OH. The synergistic effect of the supported ruthenium nanoparticles and black titanium dioxide gives the catalyst excellent activity and carbon monoxide selectivity in the carbon dioxide reduction reaction.

[0025] 4. In-situ active site construction technology enhances the stability of the catalyst. Since the hindered Lewis acid-base active sites in the above catalyst can be quickly regenerated under reaction conditions, the catalyst of the present invention has high catalytic activity and stability. Hydrogen is used as a reactant and also as one of the raw materials for the construction of active sites. The hydrogen overflow effect produced by the loaded ruthenium nanoparticles further hydrogenates the surface of black titanium dioxide, which is the key to the construction of reaction sites. This process is sustainable at high temperatures. The continuous introduction of hydrogen allows this site to be continuously regenerated and circulated under the reaction atmosphere, thereby stabilizing the activity of the catalyst.

[0026] In summary, the present invention provides a catalyst that can efficiently focus solar energy to activate and hydrogenate carbon dioxide to generate carbon monoxide. Through the modification of the black titanium dioxide carrier and the action of the hindered Lewis acid-base pair, the catalyst of the present invention can effectively utilize the full spectrum of light energy in the 200 nanometer to 2500 nanometer band in sunlight, and exhibits extremely high photothermal conversion capacity and carbon dioxide reduction catalytic activity. Compared with traditional ruthenium-based catalysts, the catalyst of the present invention successfully reversed the selectivity of the reaction, effectively improved the selectivity of carbon monoxide, and reduced the generation of by-products. The above processes all use concentrated sunlight for energy, which solves the problem of additional carbon emissions caused by fossil energy and has a high commercial prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 is the X-ray diffraction pattern of the Ru / BTO catalyst obtained in Example 1 of the present invention; Figure 2 is a high-resolution transmission electron microscopy image of the Ru / BTO catalyst obtained in Example 1 of the present invention; Figure 3 is a scanning transmission electron microscope photograph and energy dispersive X-ray spectrum of the Ru / BTO catalyst obtained in Example 1 of the present invention; Figure 4 is the activity of the Ru / BTO catalyst obtained in Example 1 of the present invention; Figure 5 The activity and selectivity of the Ru / BTO catalyst and the Ru / TiO2 catalyst obtained in Example 1 of the present invention; Figure 6 This is the solid-state NMR spectrum of the Ru / BTO catalyst obtained in Example 1 of the present invention; Figure 7 This is the electron paramagnetic resonance spectrum of the Ru / BTO catalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0029] Example 1

[0030] This example provides the synthesis of Ru / BTO catalyst: 1. The p25 titanium dioxide is modified by sodium borohydride calcination method. The specific steps are as follows: (1) 1 g of p25 titanium dioxide and 2 g of sodium borohydride were uniformly mixed in an agate mortar to obtain a mixture; (2) the mixture obtained in step (1) was uniformly ground under irradiation of an infrared lamp for 20 minutes, and then calcined in a muffle furnace at a temperature of 300 degrees Celsius for 60 minutes to obtain a black powder; (3) The black powder obtained in step (2) is placed in a beaker and 10 ml of distilled water is added thereto. At this time, the black powder reacts violently and releases heat, while releasing a large amount of gas. After the gas release stops, the product is further washed three times by centrifugation with distilled water, and finally washed three times with ethanol. The obtained product is dried by irradiation with an infrared lamp for 1 hour under an inert atmosphere of argon to obtain BTO; note here: the product must be completely cooled before it can be transferred out of the inert atmosphere, otherwise the highly active BTO may spontaneously ignite when it encounters air.

[0031] 2. Use the impregnation-photoreduction method to load modify BTO. The specific steps are as follows: (1) Disperse 1 gram of the obtained BTO in a solution containing a ruthenium precursor, using ruthenium dodecacarbonyl as the ruthenium precursor; the solvent is tetrahydrofuran. The actual ruthenium content in the solution is configured according to the required ruthenium mass ratio (1%). The suspension formed by BTO and the precursor solution is uniformly mixed after 40 minutes of ultrasound, and then transferred to a magnetic stirrer and stirred for 4 hours, so that the ruthenium precursor is fully adsorbed on the carrier BTO; (2) the suspension is then transferred to a rotary distiller and the solvent is removed by vacuum distillation in a water bath at 60 degrees Celsius to obtain a catalyst precursor; (3) The catalyst precursor was placed in a quartz reactor and subjected to light reduction in a reducing atmosphere. The reducing atmosphere was a hydrogen-argon mixture (the volume ratio of hydrogen to argon was 1:3, and the total flow rate was 100 mL / min). The reduction temperature was 200 degrees Celsius and the reduction time was 8 hours. After reduction, a Ru / BTO catalyst with a loading of 1 wt% was obtained. In the reduction process, a xenon lamp was the only light source. The temperature control was tested by directly contacting the catalyst surface with a thermistor probe. The gas flow was controlled by an electronic flow meter. The reactor carrying the catalyst was made of quartz. The obtained Ru / BTO catalyst was structurally characterized. The results are shown in Figure 1 , Figure 2 and Figure 3 .

[0032] Example 2

[0033] This example provides the synthesis of Ru / BTO catalyst: 1. The p25 titanium dioxide is modified by lithium aluminum hydride calcination method. The specific steps are as follows: (1) 1 g of p25 titanium dioxide and 4 g of lithium aluminum hydride were uniformly mixed in an agate mortar to obtain a mixture; (2) the mixture obtained in step (1) was uniformly ground under irradiation of an infrared lamp for 30 minutes, and then calcined in a muffle furnace at a temperature of 240 degrees Celsius for 30 minutes to obtain a black powder; (3) The black powder obtained in step (2) is placed in a beaker and 10 ml of distilled water is added thereto. At this time, the black powder reacts violently and releases heat, while releasing a large amount of gas. After the gas release stops, the product is further washed three times by centrifugation with distilled water, and finally washed three times with ethanol. The obtained product is dried by irradiation with an infrared lamp for 1 hour under an inert atmosphere of argon to obtain BTO; note here: the product must be completely cooled before it can be transferred out of the inert atmosphere, otherwise the highly active BTO may spontaneously ignite when it encounters air.

[0034] 2. Use the impregnation-photoreduction method to load modify BTO. The specific steps are as follows: (1) Disperse 1 gram of the obtained BTO in a solution containing a ruthenium precursor, using ruthenium chloride as the ruthenium precursor; the solvent is ethanol. The actual ruthenium content in the solution is configured according to the required ruthenium mass ratio (2%). The suspension formed by BTO and the precursor solution is evenly mixed after 40 minutes of ultrasound, and then transferred to a magnetic stirrer and stirred for 4 hours, so that the ruthenium precursor is fully adsorbed on the carrier BTO; (2) the suspension is then transferred to a rotary distiller and the solvent is removed by vacuum distillation in a water bath at 70 degrees Celsius to obtain a catalyst precursor; (3) The catalyst precursor was placed in a quartz reactor and subjected to light reduction in a reducing atmosphere, the reducing atmosphere being a hydrogen-argon mixture (ratio 3:1, total flow rate 100 mL / min), the reduction temperature being 250 degrees Celsius, the reduction time being 8 hours, and a Ru / BTO catalyst with a loading of 2 wt% was obtained after reduction. In the reduction process, a xenon lamp was the only light source, the temperature control was tested by directly contacting the catalyst surface with a thermistor probe, the gas flow was controlled by an electronic flow meter, and the reactor carrying the catalyst was made of quartz.

[0035] Example 3

[0036] This example provides the synthesis of Ru / BTO catalyst: 1. Modify p25 titanium dioxide by sodium hydride calcination method. The specific steps are as follows: (1) 1 g of p25 titanium dioxide and 1 g of sodium hydride were uniformly mixed in an agate mortar to obtain a mixture; it should be noted that sodium hydride is more chemically active than sodium borohydride and lithium aluminum hydride in Examples 1 and 2, and should be handled in a dry environment to ensure safety; (2) grinding the mixture obtained in step (1) uniformly under irradiation of an infrared lamp for 10 minutes, and then calcining it in a muffle furnace at a temperature of 200 degrees Celsius for 10 minutes to obtain a black powder; (3) The black powder obtained in step (2) is placed in a beaker, and 40 ml of a 50% ethanol aqueous solution is added thereto. At this time, the black powder reacts violently and releases heat, while releasing a large amount of gas. After the gas release stops, the product is further washed three times by centrifugation with distilled water, and finally washed three times with ethanol. The obtained product is dried by irradiation with an infrared lamp for 1 hour under an inert atmosphere of argon to obtain BTO; note here: the product must be completely cooled before it can be transferred out of the inert atmosphere, otherwise the highly active BTO may spontaneously ignite when it encounters air.

[0037] 2. Use the impregnation-photoreduction method to load modify BTO. The specific steps are as follows: (1) Disperse 1 gram of the obtained BTO in a solution containing a ruthenium precursor, using ruthenium acetylacetonate as the ruthenium precursor; the solvent is acetone. The actual ruthenium content in the solution is configured according to the required ruthenium mass ratio (5%). The suspension formed by BTO and the precursor solution is uniformly mixed after 30 minutes of ultrasound, and then transferred to a magnetic stirrer and stirred for 4 hours, so that the ruthenium precursor is fully adsorbed on the carrier BTO; (2) the suspension is then transferred to a rotary distiller and the solvent is removed by vacuum distillation in a water bath at 40 degrees Celsius to obtain a catalyst precursor; (3) The catalyst precursor was placed in a quartz reactor and subjected to light reduction in a reducing atmosphere, wherein the reducing atmosphere was a hydrogen-argon mixture (ratio 1:1, total flow rate 100 mL / min), the reduction temperature was 350 degrees Celsius, the reduction time was 8 hours, and after reduction, a Ru / BTO catalyst with a loading of 5 wt% was obtained. In the reduction process, a xenon lamp was the only light source, and the temperature control was tested by directly contacting the catalyst surface with a thermistor probe, wherein the gas flow was controlled by an electronic flow meter, and the reactor carrying the catalyst was made of quartz.

[0038] Comparative Example 1 This comparative example provides a specific preparation method of unmodified Ru / TiO2, and uses an impregnation-photoreduction method to load-modify the unmodified TiO2. The specific steps are as follows: (1) Disperse 1 gram of unmodified TiO2 in a solution containing a ruthenium precursor, using ruthenium dodecacarbonyl as the ruthenium precursor; the solvent is tetrahydrofuran. The actual ruthenium content in the solution is configured according to the required ruthenium mass ratio (1wt%). The suspension formed by the unmodified TiO2 and the ruthenium precursor solution is uniformly mixed after ultrasonic treatment for 40 minutes, and then transferred to a magnetic stirrer and stirred for 4 hours, so that the ruthenium precursor is fully adsorbed on the unmodified TiO2.

[0039] (2) The suspension was then transferred to a rotary distiller and the solvent was removed by vacuum distillation at 60 °C in a water bath to obtain a catalyst precursor.

[0040] (3) The catalyst precursor is placed in a quartz reactor and subjected to light reduction in a reducing atmosphere, wherein the reducing atmosphere is a hydrogen-argon mixed gas (the volume ratio of hydrogen to argon is 1:3, and the total flow rate is 100 mL / min), the reduction temperature is 200 degrees Celsius, and the reduction time is 8 hours. After reduction, a Ru / TiO2 catalyst with a loading amount of 1 wt% of ruthenium nanoparticles is obtained. During the reduction process, a xenon lamp is the only light source, wherein the temperature control is tested by directly contacting the catalyst surface with a thermistor probe, wherein the gas flow rate is controlled by an electronic flow meter, and wherein the reactor carrying the catalyst must be made of quartz.

[0041] Structural characterization and performance testing Structural characterization: (1) X-ray diffraction patterns of Ru / BTO with a ruthenium nanoparticle loading of 1 wt% obtained in Example 1 and Ru / TiO2 in Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the modified Ru / BTO is an amorphous structure, while the unmodified Ru / TiO2 shows a diffraction signal attributable to TiO2 in the X-ray diffraction pattern. No Ru-related signals are seen in the X-ray diffraction patterns of the two, indicating that the size of the Ru nanoparticles is small.

[0042] (2) High-resolution transmission electron microscopy images of Ru / BTO with a ruthenium nanoparticle loading of 1 wt% are shown in Figure 2 It can be seen that its lattice structure completely disappears and it is in an amorphous state, which is consistent with the results of X-ray diffraction. The scanning transmission electron microscopy image and energy dispersive X-ray element distribution map of Ru / BTO with a ruthenium nanoparticle loading of 1 wt% are shown in Figure 3 , which indicates that the Ru nanoparticles are uniformly loaded on the surface of the carrier BTO.

[0043] (3) Identification of active sites on the catalyst surface In order to identify the special active sites on the surface of Ru / BTO catalyst, solid-state nuclear magnetic resonance and paramagnetic electron resonance characterization were carried out on Ru / BTO catalyst. Figure 6 and Figure 7. Solid-state NMR results show that there are a large number of surface hydroxyl groups Ti-OH and titanium-hydrogen bonds Ti-H on the surface of Ru / BTO, which are new active sites that do not exist in conventional titanium dioxide supported catalysts. Electron paramagnetic resonance results further show that titanium-hydrogen bonds exist in the form of hydrogen-carrying oxygen vacancies. In the electron paramagnetic resonance spectrum, fine structural splitting of the signal appears, which is attributed to the oxygen vacancies doped with hydrogen, namely Ti-HOV, which is also a new active site that does not exist in conventional oxygen vacancy catalysts. The hydrogen in Ti-HOV on the catalyst surface carries a partial negative charge and is a Lewis base; the hydrogen in Ti-OH carries a partial positive charge and is a Lewis acid, Ti-HOV and Ti-OH. The two are not connected by chemical bonds, but are discrete in space, forming a hindered Lewis acid-base pair Ti-HOV···Ti-OH. This active site can directly activate an oxygen atom in gaseous carbon dioxide and generate water and carbon monoxide. In a hydrogenation atmosphere, the ruthenium nanoparticles loaded on the BTO surface can efficiently activate hydrogen to produce hydrogen overflow, which further hydrogenates the BTO surface and replenishes the consumed Ti-HOV···Ti-OH. Based on this, the synergistic effect of the loaded ruthenium nanoparticles and black titanium dioxide reverses the methane selectivity of conventional ruthenium-based catalysts in the photothermal reduction of carbon dioxide, making the catalyst have excellent activity and carbon monoxide selectivity in the carbon dioxide reduction reaction.

[0044] Performance Testing 1. Photothermal activity test of catalyst: Place the catalyst in a quartz reactor, introduce carbon dioxide and hydrogen in a volume ratio of 1:1, and then measure the temperature of the catalyst surface under the irradiation of simulated sunlight concentrated by a xenon lamp as the light source. The results are shown in Figure 4 The results show that the temperature of the catalyst surface can be raised to over 200 degrees Celsius under light. As the temperature rises, the activity of the catalyst in photothermal reduction of carbon dioxide to produce carbon monoxide also increases, and the activity can reach over 10 mmol CO / g catalyst / hour. Figure 5 It can also be seen that the carbon monoxide selectivity of Ru / BTO obtained in Example 1 is much higher than that of Ru / TiO2 in Comparative Example 1, while Ru / TiO2 mainly produces methane.

[0045] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A black titanium dioxide composite material loaded with ruthenium nanoparticles, characterized in that: Black titanium dioxide is used as a carrier, and ruthenium nanoparticles are loaded on the surface of the carrier, and the surface of the carrier contains a Ti-H···Ti-OH hindered Lewis acid-base pair.

2. The black titanium dioxide composite material loaded with ruthenium nanoparticles according to claim 1, characterized in that: The loading amount of the ruthenium nanoparticles is 0.5wt%-5wt%; The average particle size of the ruthenium nanoparticles is 2-5 nanometers.

3. A method for preparing a black titanium dioxide composite material loaded with ruthenium nanoparticles as claimed in claim 1 or 2, characterized in that: The following steps are involved: P25 titanium dioxide and a reducing agent are mixed, the resulting mixture is light-milled, and then heated and calcined to obtain a black powder; The obtained black powder is mixed with water for reaction, the solid-liquid separation is performed to obtain a solid phase, and the obtained solid phase is dried under light in an inert atmosphere to obtain modified titanium dioxide BTO; Dispersing modified titanium dioxide BTO in a ruthenium-containing precursor solution to obtain a suspension; removing the solvent in the suspension to obtain a precursor; The precursor is photo-reduced in a reducing atmosphere to obtain the black titanium dioxide composite material loaded with ruthenium nanoparticles.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the p25 titanium dioxide to the reducing agent is 1:(2-4); The reducing agent is selected from one or more of sodium borohydride, potassium borohydride, lithium aluminum hydride, sodium hydride and lithium hydride; The heating calcination temperature is 300-500°C and the time is 60-120 minutes.

5. The preparation method according to claim 3, characterized in that: The ruthenium-containing precursor in the ruthenium-containing precursor solution is selected from one or more of ruthenium dodecacarbonyl, ruthenium chloride, ruthenium acetylacetonate, and ruthenium acetate; The solvent of the ruthenium-containing precursor solution is selected from one or more of methanol, ethanol, tetrahydrofuran, acetone, and cyclohexane; The ruthenium concentration in the ruthenium-containing precursor solution is 100-2000 ppm; The inert gas in the inert atmosphere is selected from one or more of nitrogen, argon, helium and neon; The light source in the light drying is infrared light, and the light exposure time is 1 to 3 hours.

6. The preparation method according to claim 3, characterized in that: The mass ratio of ruthenium loaded in the modified titanium dioxide BTO is 0.1-5 wt%.

7. The preparation method according to claim 3, characterized in that: The reducing gas in the reducing atmosphere includes hydrogen and an inactive gas, wherein the inactive gas is selected from one or more of nitrogen, argon, helium and neon; The volume ratio of hydrogen to inert gas is (3:1)-(1:3); The total gas flow rate in the reducing atmosphere is 50-100 mL / min; The temperature of light reduction is 200-280℃ and the time is 4-8h.

8. Use of the black titanium dioxide composite material loaded with ruthenium nanoparticles according to claim 1 or 2 in photothermal catalytic reduction of carbon dioxide to carbon monoxide.

9. The use according to claim 8, characterized in that: A mixed gas of carbon dioxide and hydrogen is introduced into the photothermal catalytic reaction; Wherein, the volume ratio of carbon dioxide to hydrogen is (4:1)-(1:4); The reaction temperature in the photothermal catalytic reaction is greater than or equal to 200°C.

10. The use according to claim 9, characterized in that: Before the photocatalytic reaction, the black titanium dioxide composite material loaded with ruthenium nanoparticles needs to be activated. The activation conditions are: 180-300°C and irradiation in a reducing atmosphere for 6-8 hours.

Citation Information

Patent Citations

  • Noble metal-carrying titanium dioxide catalyst and preparation method and use thereof

    CN102120184A

  • Black titanium dioxide composite catalyst for photoreduction of carbon dioxide and preparation method of composite catalyst

    CN108404956A

  • TiO2-supported ruthenium catalyst and preparation method thereof

    CN108686635A

  • TiO2-x-based hindered Lewis acid-base pair photocatalyst as well as preparation method and application thereof

    CN112569919A

  • Catalyst Pt / TiN, preparation method thereof and application of catalyst Pt / TiN in photocatalytic reduction of carbon dioxide to carbon monoxide

    CN118341469A

Cited By

  • Hydroxyl-rich ruthenium / titanium dioxide catalyst as well as preparation method and application thereof

    CN120939932A